Rare Cause of Stricture Esophagus—Sarcoma: A Case Report and Review of the literature. (13th October 2011) - Patricia, S.; Saikat, Das; Rajesh, B.; Rajesh, I.; Selvamani, B.; Subhashini, John
Abstract : Adenocarcinoma and squamous cell carcinoma account for the vast majority of oesophageal malignancies. Other malignancies known to occur in the oesophagus include melanoma, sarcoma, and lymphoma. Among the sarcomas, carcinosarcoma is the commonest with both carcinomatous and sarcomatous elements followed by leiomyosarcoma of mesenchymal origin. Other sarcomas reported in the literature are liposarcoma, synovial sarcoma, myxofibrosarcoma, Ewing's sarcoma, granulocytic sarcoma, histiocytic sarcoma, schwannoma rhabdomyosarcoma, and epithelioid sarcoma. We report a case of malignant spindle cell tumour of oesophagus. Sarcomas of esophagus present as a polypoid exophytic soft tissue mass. Our patient presented with a stricture which is a rare presentation. Locally aggressive treatment with surgery is beneficial, and local palliative treatment including radiotherapy is worthwhile.